AN INVESTIGATION OF PROFESSIONAL DEVELOPMENT OF ENGLISH TEACHER IN PRIMARY SCHOOL SETTING: A CASE STUDY - Miyarti, Miyarti; Inawati, Iin; Khafifah, Maharani Nur; Henu, Nur; Damayanti, Retno Vinsi; Aisyah, Shifak (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This study is aimed at investigating the program teachers' professional development (TPD) during their time as primary teachers and the reasons for their professional advancement. The method of the study can be categorized as case study research which aims at understanding complex events by studying them in their normal environment. The findings show that there are three programs of TPD; Teachers Supporting Group (Kelompok Kerja Guru/KKG), webinar and courses that teachers do to improve their professionalism in teaching. This study indicates that a variety of requirements and circumstances determine why teachers engage in professional development. Teacher 1 does TPD to know updated information about teaching material and the latest information about the examination. She also attended the KKG because she was motivated to complete the teacher’s administration. Meanwhile, teacher 2 does TPD to improve her teaching skill as she is a new teacher in the school.